Trans -resveratrol, piceatannol and gallic acid: potent polyphenols isolated from Mezoneuron benthamianum effective as anticaries, antioxidant and cytotoxic agents (2020)
Phytochemical investigation of the ethyl acetate extract of the root of Mezoneuron ben- thamianum , a shrub commonly used as chewing stick in the southwest of Nigeria, led to the isolation of three compounds characterised as trans -resveratrol, piceatannol and gallic acid by the use of spectroscopic techniques. The anticaries activity of the polyphenols was evaluated against four oral bacteria pathogens ( Streptococcus mutans, Pseudomonas aerugi- nosa, Staphylococcus aureus and Escherichia coli), isolated from clinical samples presented by patients having dental caries, while their antioxidant and cytotoxic activities were deter- mined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and brine shrimp ( artemia salina nau- plii) bioassay techniques. The results showed that the isolated compounds exhibited very strong anticaries activity with minimum inhibitory concentration (MIC) ranging from 25 to 300 μg/ml, antioxidant activity with IC 50 of 35.81, 30.35 and 11.73 μg/ml, when com- pared with ascorbic acid (IC 50 = 38.20 μg/ml) and cytotoxic activity with LC 50 of 7.15, 99.99 and 98.71 μg/ml for resveratrol, piceatannol and gallic acid respectively The isolated compounds demonstrated very strong anticaries, antioxidant and cytotoxic activities. This study further justifies the ethno-medicinal use of M. benthamianum as an effective tool in maintaining oral hygiene.